Dari Keterbatasan Menjadi Kekuatan: Inovasi Ekowisata Berbasis Produk Lokal untuk Transformasi Ekonomi Wanita Disabilitas Di Sumatera Utara - Yusrita, Yusrita; Rahayu, Sri; Triastuti, Henny; Riana, Zenny (Forum Kerjasama Pendidikan Tinggi, 2025)
This community service program aimed to enhance the entrepreneurial capacity of women with disabilities through local product–based ecotourism innovation in North Sumatra, Indonesia. The initiative originated from the limited ability of disabled entrepreneurs to utilize digital marketing strategies, manage simple financial records, and create innovative products that meet tourism market demands. The partners comprised twenty female participants from the Indonesian Women with Disabilities Association (HDWI), representing diverse regions such as Medan, Binjai, Parapat, and Sidikalang, and various business types including rattan crafts, batik, coffee processing, and traditional food production. The implementation methods included needs assessment, interactive training, participatory mentoring, and evaluation through surveys and observations. The results indicated substantial improvements in participants’ knowledge and skills, particularly in packaging innovation, product differentiation, and the use of social media for business promotion. Participants also began to apply basic financial recording and established interregional business networks to expand their market reach. This activity contributed positively to economic independence and social participation among women with disabilities in the ecotourism sector. Nevertheless, the short mentoring duration and limited access to digital technology remained major challenges. The program recommends ongoing mentoring and digital empowerment to ensure broader and sustainable impacts.